Method for creating separator plate for fuel cells configured by covering entire sheet-like compact consisting of synthetic resin with set of aggregates of carbon blacks bonded by frictional pressure contact
A carbon black aggregate network formed through compression and vibration processes addresses the challenges of electrical resistance, gas permeability, and cost-effectiveness in fuel cell separator plates, resulting in a lightweight, corrosion-resistant, and cost-effective solution for fuel cell applications.
Patent Information
- Application Number
- JP2023119530
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-23
- Publication Date
- 2025-02-04
AI Technical Summary
Existing fuel cell separator plates made of synthetic resin substrates face challenges in achieving low electrical resistance, gas permeability, corrosion resistance, strength, and cost-effectiveness, while current methods to enhance conductivity often result in increased manufacturing complexity and material costs.
A method involving the creation of a separator plate composed of a carbon black aggregate network formed by crushing and redistributing carbon black in methanol, followed by a series of compression and vibration processes to interlock the aggregates at a frictional pressure, resulting in a sheet-shaped molded body with integrated grooves and protrusions for gas passage.
The solution achieves a separator plate with reduced electrical resistance, optimal gas permeability, enhanced corrosion resistance, and lower manufacturing costs, while maintaining lightweight and impact-resistant properties, meeting the requirements for fuel cell applications.
Smart Images

Figure 2025016417000001_ABST
Abstract
Description
[Technical field]
[0001] In the present invention, a sheet-shaped fuel cell separator plate is produced by successively carrying out the following processes. First, a sheet-like molding is formed from a synthetic resin having a plurality of grooves on one surface through which hydrogen gas passes and a plurality of grooves on the other surface through which oxygen gas or air passes. Next, a first plate material is molded from a synthetic resin having the same shape as the sheet-like molded body but a greater thickness than the sheet-like molded body, and having a plurality of protrusions formed at positions corresponding to the plurality of grooves formed in the sheet-like molded body through which hydrogen gas passes, the protrusions having shapes that overlap the plurality of grooves. Furthermore, a second plate material is molded, which is made of synthetic resin and has the same shape as the sheet-like molded body, a thickness greater than that of the sheet-like molded body, and which has a plurality of protrusions formed at positions corresponding to the plurality of grooves formed in the sheet-like molded body through which oxygen gas or air passes, the protrusions having shapes that overlap the plurality of grooves. Thereafter, a third plate material that covers the entire carbon black clusters immersed in methanol is placed over the carbon black clusters, and the entire surface of the third plate material is uniformly compressed to crush the carbon black clusters. Furthermore, vibration acceleration in three directions is repeatedly applied to the crushed carbon black clusters, and the crushed carbon black clusters are rearranged in methanol. These paired processes of applying a compressive load and applying a vibration acceleration are repeated to crush the carbon black clusters immersed in methanol to their limit size. Furthermore, a homogenizer device is operated in methanol, and shock waves are repeatedly applied to the crushed carbon black clusters via methanol to separate the entanglement of the aggregates in the carbon black, entangle the aggregates via methanol, and further create a suspension in which the entangled aggregate clusters are dispersed in methanol. Furthermore, an alcohol that is soluble or miscible in methanol, has a viscosity 9-20 times that of methanol, and has a boiling point higher than that of methanol but lower than 200°C, is mixed into the suspension in such a ratio that the viscosity of the suspension increases 5-10 times, creating a new suspension in which a collection of entangled aggregates is dispersed in an alcohol solution having a viscosity of 3-6 mPa·sec at 20°C. Thereafter, a new suspension is poured into a container having a bottom shape slightly larger than the sheet-like molded product, and the sheet-like molded product is further immersed in the new suspension. Furthermore, the first plate is placed in a container having a rectangular bottom surface, in which each plate constituting the four sides of the container has a function of moving in parallel to the side in a direction perpendicular to the side, so that the multiple protrusions of the first plate are placed on top of the container, and the sheet-like molded body immersed in the new suspension is placed on the first plate so that the multiple grooves of the sheet-like molded body through which hydrogen gas passes overlap with the multiple protrusions of the first plate. Furthermore, the second plate is placed on the sheet-like molded body so that the multiple grooves of the sheet-like molded body through which oxygen gas or air passes overlap with the multiple protrusions of the second plate. After this, a compressive load is evenly applied to the entire surface of the second plate, and the container is heated to the boiling point of the alcohol. Furthermore, each plate constituting the upper and lower sides of the container is moved in parallel to the inside of the container at the same time, and the upper and lower sides of the sheet-like molded body are compressed with a compressive stress equivalent to the compressive load, and then each plate constituting the upper and lower sides is returned to its original position. Furthermore, the plate materials constituting the left and right side surfaces of the container are simultaneously moved in parallel toward the inside of the container, the left and right side surfaces of the sheet-like compact are compressed with a compressive stress equivalent to the compressive load, and then the plate materials constituting the left and right side surfaces are returned to their original positions. As a result, after the methanol and alcohol are evaporated from the new suspension, a compressive stress is applied to the collection of entangled aggregates covering the entire sheet-like compact, the entangled aggregates are frictionally welded to each other, and further, the frictionally welded collection of aggregates is frictionally welded to the entire sheet-like compact, so that the entire sheet-like compact is covered with the collection of aggregates joined by friction welding. After this, the same impact acceleration is applied simultaneously to multiple locations on the bottom surface of the container, and the sheet-like molded body covered with the aggregate collection bonded to both the first plate and the second plate is peeled off from the container. Further, the same impact acceleration is applied simultaneously to multiple locations on the bottom surface of the first plate, and the sheet-like molded body covered with the aggregate collection is peeled off from the first plate. Finally, the same impact acceleration is applied simultaneously to multiple locations on the surface of the second plate, and the sheet-like molded body covered with the aggregate collection is peeled off from the second plate. The result is a fuel cell separator plate covered with a collection of friction welded aggregates.
[0002] The present inventors have filed a patent application (Japanese Patent Application No. 2021-035897) for an invention relating to a method for repeatedly adsorbing carbon black aggregates onto synthetic resin pellets and using the collection of synthetic resin pellets to mold a molded body having the shape of a fuel cell separator plate. The present invention differs from the prior application in that a sheet-like molded body made of synthetic resin that constitutes the fuel cell separator plate is prepared in advance, and a group of aggregates joined by friction welding is friction-welded to the front and side surfaces of the sheet-like molded body. Therefore, the fuel cell separator plate of the present invention can be prepared more cheaply than the fuel cell separator plate of the prior application. In addition, since the sheet-like molded body of synthetic resin is prepared in advance, there are no restrictions on the material and shape of the molded body. [Background technology]
[0003] Polymer electrolyte fuel cells are being considered for use as power sources for electric vehicle power generation equipment, home cogeneration systems, and portable devices such as personal computers. In polymer electrolyte fuel cells, unit cells are stacked and arranged in series to generate a large electromotive force. Separator plates are used to separate the unit cells. For example, one electric vehicle requires as many as 400 separator plates. Thus, the separator plates account for the majority of the weight and cost of a fuel cell. For this reason, in order to popularize polymer electrolyte fuel cells, it is essential to both significantly reduce the cost and weight of separator plates. On the other hand, the separator plate is required to have the functions of electrical conductivity, gas impermeability, corrosion resistance, strength, and gas supply property, as well as low cost. First, the electrical resistance of the separator plate causes power generation loss in the polymer electrolyte fuel cell and also causes heat generation. Heat generation shortens the life of the cell, so it is necessary to increase the cooling capacity of the cell. Adding a cooler further increases the weight and manufacturing cost of the cell. Incidentally, the electrical resistance of the separator plate required by the US Department of Energy is 20Ωcm or less. However, automobile fuel cells are required to generate power of about 90kW. For example, in a 300-volt, 300-amp fuel cell, if a material with an electrical resistance of 20Ωcm is used, and the resistance when current flows through 400 separator plates with an area of A-4 and a thickness of 2mm is only 0.0026Ω, when a current of 300 amp flows through these separator plates, a voltage loss of 0.8 volts occurs, resulting in an internal loss of 240 watts and heat generation. For this reason, it is necessary to increase the cooling capacity of the cell by using a cooler. Therefore, the lower the electrical resistance of the separator plate, the better. Secondly, hydrogen gas and oxygen gas (or air) flow on the front and back of the separator plate, and if the hydrogen gas and oxygen gas (or air) mix together, it can cause an explosion and fuel loss. For this reason, the separator plate is required to be gas impermeable at atmospheric pressure. Incidentally, the gas impermeability required by the US Department of Energy for separator plates is 2 x 10 ―6 cm 3 / cm 2 / second. Third, the principle of power generation in fuel cells is the use of protons (H + ) moves from the fuel electrode to the oxygen electrode. For this reason, electricity is generated in a strongly oxidizing environment, which requires the separator plate to have high corrosion resistance. Metals that can be used in this environment are limited to gold and platinum due to their high corrosion potential. Therefore, the metal used for the separator plate must be gold plated, which increases the manufacturing cost of the separator plate. Furthermore, if metal ions dissolve into the battery, the dissolved metal ions reduce the power generation capacity of the polymer membrane. For this reason, the metal used for the separator plate must be gold plated. Fourth, fuel cells in automobiles are required to withstand the impact of a collision, so the separator plates need to be strong. On the other hand, if the separator plates are made thicker to increase their strength, the weight of the separator plates will increase. Fifth, the separator plate has the function of supplying hydrogen gas and oxygen gas (or air) to the polymer membrane. For this reason, the separator plate needs to be able to supply gas. In many cases, grooves are formed in the separator plate and used as passages for supplying gas. Sixth, the key technology for the widespread use of electric vehicles is a significant reduction in the manufacturing costs of solid polymer electrolyte fuel cells. Therefore, in order to popularize electric vehicles, it is necessary to significantly reduce the cost of separator plates currently being developed. Therefore, it is necessary to develop new separator plates that are completely different in composition and structure from those currently being developed. The materials of separator plates currently being developed are roughly divided into metal-based and carbon-based. From the viewpoints of weight reduction, reduction in manufacturing costs, and ensuring corrosion resistance, separator plates made of a synthetic resin substrate and a carbon-based material that provides electrical conductivity are superior to separator plates made of other materials. That is, the density of general-purpose synthetic resins is 0.9-1.6 g / cm. 3 The density of aluminum is 2.7g / cm 3 The cost of forming a separator plate from synthetic resin is lower than the cost of processing a separator plate from metal. Furthermore, general-purpose carbon materials such as carbon black and graphite particles are cheaper than metal particles. Carbon materials also have better corrosion resistance than metal particles.
[0004] As a conventional example of imparting electrical conductivity to a synthetic resin substrate by using a carbon-based material, for example, there is the following conventional technology. Patent Document 1 describes a separator plate in which a conductive composition is spray-coated on the uneven surface of a substrate made of various synthetic resins. The conductive composition uses a resin such as epoxy resin, silicon resin, polyimide resin, phenol resin, or acrylic resin as a binder, and conductive carbon powder or metal powder such as Ag, Cu, or Ni is dispersed in the binder. However, even if conductive carbon powder or metal powder is simply dispersed in a synthetic resin binder, unless the conductive carbon powder or metal powder is continuously bonded to form a path for current flow, the electrical resistance of the synthetic resin binder becomes dominant, and the conductivity of the separator plate does not improve. On the other hand, in order to increase the conductivity of the separator plate, it is necessary to increase the filling rate of the conductive carbon powder or metal powder, but increasing the filling rate of these solids makes spray coating difficult. In addition, when metal powder is used, the metal powder that appears on the surface dissolves, which causes internal corrosion of the separator plate.
[0005] Patent Document 2 describes a conductive separator plate that is a composite of a non-carbonaceous resin made of synthetic resin and a conductive agent made of spherical graphite, graphite powder with an aspect ratio of 2.0 or less, and conductive carbon black. However, even if a conductive agent is simply mixed into a non-carbonaceous resin and molded into a compact, unless the conductive agent is continuously bonded to form a path through which an electric current can flow in the compact, the electrical resistance of the non-carbonaceous resin becomes dominant and the conductivity of the separator plate does not improve. On the other hand, if the filling rate of the conductive agent is increased in order to increase the conductivity of the separator plate, molding the non-carbonaceous resin becomes difficult. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2004-079536 [Patent Document 2] WO99 / 49530 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0007] The following six challenges arise when forming a separator plate that provides conductivity using a carbon-based material on a substrate made of synthetic resin. First, there is a problem of making the electrical resistance of the separator plate closer to that of the carbon-based material, so that the carbon-based material forms continuous paths in the synthetic resin substrate, and electrons move through the paths, so that the electrical resistance of the synthetic resin substrate approaches that of the carbon-based material. On the other hand, as explained in paragraphs 4 and 5, simply mixing an insulating material with a conductive material does not allow the conductive materials to bond or come into contact with each other and form a continuous path for electrons to move in the synthetic resin substrate. In contrast, if the entire synthetic resin substrate can be covered with a highly conductive carbon-based material, the carbon-based material will form a continuous path in the synthetic resin substrate, and the electrical resistance of the synthetic resin substrate will approach the electrical resistance of the carbon-based material. Therefore, the second challenge is to find an inexpensive method for covering the entire synthetic resin substrate with a highly conductive carbon-based material. Furthermore, the separator plate has the function of supplying hydrogen gas and oxygen gas (or air) to the polymer membrane. Therefore, the third challenge is to ensure that the highly conductive carbon-based material covering the synthetic resin substrate does not impede the movement of hydrogen gas and oxygen gas (or air) and that the grooves provided in the synthetic resin substrate are able to supply hydrogen gas and oxygen gas (or air) to the polymer membrane. In addition, the separator plate must have a strength sufficient to prevent it from breaking even when subjected to an impact force. Therefore, the fourth problem is that the synthetic resin substrate must be able to withstand the impact force when it is subjected to the impact force. For this reason, it is necessary to mold the substrate with a synthetic resin having a high impact strength. In addition, it is necessary that the highly conductive carbon-based material does not peel off from the synthetic resin substrate when it is subjected to the impact force. For this reason, it is necessary for the highly conductive carbon-based material to be bonded to the substrate with a large bonding force by the synthetic resin. Furthermore, if the highly conductive carbon-based material covering the synthetic resin substrate is lightweight, the impact force received by the highly conductive carbon-based material is small. For this reason, it is necessary for the highly conductive carbon-based material covering the synthetic resin molded body to be lightweight. In addition, if the highly conductive carbon-based material can be elastically deformed when it is subjected to the impact force, the highly conductive carbon-based material can withstand the impact force. For this reason, it is necessary for the highly conductive carbon-based material to be elastically deformed when it is subjected to the impact force. Furthermore, in order to popularize fuel cells, it is required that the weight of the separator plate is significantly lighter than that of conventionally developed separator plates, and that the manufacturing cost of the separator plate is significantly lower than that of conventionally developed separator plates. Therefore, the fifth problem is that the separator plate needs to be made with a very simple process, and all of the materials used must be inexpensive, general-purpose industrial materials. Furthermore, the synthetic resin substrate and the highly conductive carbon-based material covering the substrate need to be lightweight. The problem that the present invention aims to solve is to solve the above five problems and to find a method for producing a separator plate made of a substrate of a synthetic resin to which electrical conductivity has been imparted. [Means for solving the problem]
[0008] A method for producing a separator plate for a fuel cell, which has a structure in which a sheet-like molded body made of a synthetic resin is entirely covered with a collection of carbon black aggregates bonded by friction welding, comprises the steps of: A first step of forming a sheet-like molded body made of a synthetic resin having a plurality of grooves formed on one surface through which hydrogen gas passes and a plurality of grooves formed on the other surface through which oxygen gas or air passes; a second step of molding a first plate material made of synthetic resin, the first plate material having the same shape as the sheet-like molded body, a thickness greater than that of the sheet-like molded body, and having a plurality of protrusions formed at positions corresponding to the plurality of grooves through which hydrogen gas passes, the plurality of protrusions being shaped to overlap the plurality of grooves formed in the sheet-like molded body; a third step of molding a second plate material made of synthetic resin, the second plate material having the same shape as the sheet-like molded body, a thickness greater than that of the sheet-like molded body, and having a plurality of protrusions formed at positions corresponding to the plurality of grooves through which oxygen gas or air passes, the plurality of protrusions being shaped to overlap the plurality of grooves formed in the sheet-like molded body; A first suspension is prepared by placing carbon black clumps and methanol in a quantity greater than the weight of the carbon black clumps in a first container, stirring the methanol, and immersing the carbon black clumps in the methanol. Thereafter, a third plate material that covers the entire surface of the first suspension is placed on top of the first suspension, and a compressive load is applied evenly to the entire surface of the third plate material to crush the carbon black clumps immersed in the methanol. The first container is placed on a vibration table of a vibrator, and the vibrator is operated to repeatedly apply vibration acceleration in three directions, front-back, left-right, and up-down, to the first container, and the crushed carbon black clumps are crushed. a fourth step of applying the compressive load evenly to the entire surface of the third plate material again to further crush the crushed carbon black clumps in the methanol; and applying the vibration acceleration in the three directions to the first container again repeatedly. The pair of steps consisting of the step of applying the compressive load and the step of applying the vibration acceleration are repeated, and when a repulsive force is generated in the third plate material when the compressive load is applied to the third plate material, it is determined that the crushing of the carbon black clumps in the methanol is completed, and the pair of steps are stopped. Then, the third plate material is removed from the first container. a fifth step of disposing a homogenizer device in the first container, operating the homogenizer device in the first suspension, and repeatedly applying shock waves to the clusters of carbon black after the crushing process via the methanol to entangle aggregates in the carbon black after the crushing process via the methanol, thereby preparing a second suspension in which the clusters of entangled aggregates are dispersed in the methanol; a sixth step of mixing an alcohol having three properties, namely, a first property of being soluble or miscible in methanol, a second property of having a viscosity 9-20 times that of methanol, and a third property of having a boiling point higher than that of methanol and lower than 200°C, with the second suspension, increasing the viscosity of a solution in which the alcohol is dissolved in the methanol or a mixture in which the alcohol is mixed to 3-6 mPa·sec at 20°C, and entangling the entangled aggregate groups through the solution or mixture, thereby preparing a third suspension in which the entangled aggregate groups are dispersed in the solution or mixture; a seventh step of pouring the third suspension into a second container having a bottom surface slightly larger than the sheet-like molded body produced in the first step, and further immersing the sheet-like molded body in the third suspension; The first plate material prepared in the second step is placed in a third container in which each plate material constituting the four side surfaces of the container has a function of moving parallel to the inside of the container in a direction perpendicular to the side surface, with the multiple protrusions formed on the first plate material facing up. Further, the sheet-like molded body immersed in the third suspension is placed on top of the first plate material so that the multiple protrusions formed on the first plate material overlap with the multiple grooves formed in the sheet-like molded body through which hydrogen gas passes. Further, the second plate material prepared in the third step is covered with the multiple protrusions formed on the first plate material. The second plate is placed on the sheet-like molded body immersed in the third suspension so that the multiple protrusions overlap the multiple grooves formed in the sheet-like molded body through which oxygen gas or air passes. Thereafter, a compressive load is evenly applied to the entire surface of the second plate, and the temperature of the third container is raised to the boiling point of the alcohol. Furthermore, each plate constituting the upper and lower side surfaces of the third container is simultaneously moved in parallel to the inside of the third container, and the upper and lower side surfaces of the sheet-like molded body immersed in the third suspension are heated to the boiling point of the alcohol. The left and right side surfaces of the sheet-like molded body immersed in the third suspension are compressed with a compressive stress corresponding to the compressive load, and then the plate materials constituting the upper and lower side surfaces are returned to their original positions. Furthermore, the plate materials constituting the left and right side surfaces of the third container are simultaneously translated toward the inside of the third container, and the left and right side surfaces of the sheet-like molded body immersed in the third suspension are compressed with a compressive stress corresponding to the compressive load, and then the plate materials constituting the left and right side surfaces are returned to their original positions. As a result, the methanol and the alcohol are vaporized from the third suspension and are mixed into the third suspension. an eighth step in which the immersed sheet-like compact is entirely covered with a collection of entangled aggregates, a compressive stress is applied to the front and side surfaces of the sheet-like compact, the entangled aggregates covering the sheet-like compact are friction-welded to each other, the compressive stress is applied to the friction-welded collection of aggregates, the friction-welded collection of aggregates is friction-welded to the front and side surfaces of the sheet-like compact, and the sheet-like compact is entirely covered with the collection of aggregates joined by friction welding; a ninth step of simultaneously applying the same impact acceleration to a plurality of positions on the bottom surface of the third container, and peeling off from the third container a sheet-like molded body covered with the aggregate collection sandwiched between the first plate and the second plate and joined to the two plates; simultaneously applying the same impact acceleration of the same magnitude to a plurality of positions on the bottom surface of the first plate, and peeling off from the first plate; and finally simultaneously applying the same impact acceleration of the same magnitude to a plurality of positions on the surface of the second plate, and peeling off from the second plate a sheet-like molded body covered with the aggregate collection; By carrying out all of these nine steps consecutively, a method for producing a fuel cell separator plate is achieved, which produces a fuel cell separator plate consisting of a sheet-like compact covered with a collection of aggregates joined by friction welding.
[0009] By continuously carrying out all the processes in the nine steps described below, a sheet-shaped fuel cell separator plate covered with a collection of aggregates joined by friction welding is produced. Here, the processes in the nine steps and the effects of the processes are described. In the first step, a sheet-like molded body is formed from a synthetic resin having a plurality of grooves on one surface through which hydrogen gas passes and a plurality of grooves on the other surface through which oxygen gas or air passes. This allows inexpensive sheet-like molded bodies to be continuously produced. On the other hand, if a sheet-like molded body can be molded, there is no restriction on the material of the synthetic resin, but the greater the impact strength, the greater the impact strength of the fuel cell separator plate. For this reason, a synthetic resin with excellent impact strength is used for a fuel cell separator plate that requires impact strength. In addition, there is no restriction on the shape and size of the sheet-like molded body. Note that a fuel cell separator plate is required to be light and thin. For this reason, a thickness of 1.5-3 mm is appropriate. This results in a fuel cell separator plate that is lighter and thinner than conventional fuel cell separator plates. On the other hand, a depth of 0.5-2.0 mm is appropriate, and it is desirable to provide the grooves so that the grooves on the front and back surfaces do not overlap. The grooves can have various shapes, and since multiple grooves are formed simultaneously on the front and back sides by molding the synthetic resin, there are no restrictions on the shape and number of the grooves. Therefore, unlike when grooves are formed by machining, the processing cost does not increase depending on the shape and number of the grooves. For example, there is a shape in which one continuous groove runs concentrically around the entire surface of the sheet-like molded body, a shape in which one continuous groove is bent 180 degrees near both ends of the sheet-like molded body and multiple linear grooves are formed in parallel at equal intervals, a shape in which one continuous groove runs around the entire surface of the sheet-like molded body as gradually smaller squares of different sizes, and a shape in which multiple linear grooves are formed in parallel at equal intervals, and so on. It is only necessary that hydrogen gas and oxygen gas or air can pass through the grooves. In the second step, a first plate material made of synthetic resin is formed, which has the same shape as the sheet-shaped molded body, a thickness greater than that of the sheet-shaped molded body, and has a plurality of protrusions formed at positions corresponding to the plurality of grooves through which hydrogen gas passes, the plurality of protrusions being formed in a shape that overlaps the plurality of grooves formed in the sheet-shaped molded body. That is, in the seventh step, the collection of entangled aggregates is adsorbed on the surface of the sheet-shaped molded body, and in the eighth step, this sheet-shaped molded body is sandwiched between the first plate material and the second plate material formed in the third step, the entire surface of the second plate material is uniformly compressed, the collection of entangled aggregates is joined by friction welding, and the collection of entangled aggregates joined by friction welding is friction welded to the sheet-shaped molded body. Therefore, as long as the first plate material can be molded, there is no restriction on the material of the synthetic resin. As for the second plate material, as long as the second plate material can be molded, there is no restriction on the material of the synthetic resin. Furthermore, since multiple protrusions are formed simultaneously by molding synthetic resin, there are no restrictions on the shape and number of protrusions, and molding costs do not depend on the shape and number of protrusions. Also, the multiple protrusions formed on the first plate overlap the multiple grooves formed on the sheet-like molded body, so they are matched to the shapes of the multiple grooves of the sheet-like molded body molded in advance. For this reason, the height of the protrusions is appropriate to be 0.5-2.0 mm. In the third step, a second plate material made of synthetic resin is molded, which has the same shape as the sheet-like molded body, a thickness greater than that of the sheet-like molded body, and has a plurality of protrusions formed at positions corresponding to the plurality of grooves through which oxygen gas or air passes, the plurality of protrusions being shaped to overlap the plurality of grooves formed in the sheet-like molded body. The plurality of protrusions formed on the second plate material are matched to the shape of the plurality of grooves in the sheet-like molded body molded previously, so that they overlap the plurality of grooves formed in the sheet-like molded body. For this reason, the height of the protrusions is appropriately 0.5-2.0 mm. In the fourth step, the carbon black clumps are immersed in methanol, and the carbon black clumps are crushed in the methanol to a limited size. For this purpose, first, the carbon black clumps and methanol in an amount greater than the weight of the carbon black clumps are put into a first container, and the methanol is stirred to prepare a first suspension in which the carbon black clumps are immersed in methanol. That is, by compressing the carbon black clumps immersed in methanol, the carbon black clumps can be easily crushed, and the crushed carbon black is dispersed in the methanol, so that the carbon black clumps are crushed by repeating the crushing of the carbon black clumps. After this, a third plate material that covers the entire surface of the first suspension is placed on the first suspension, and a compressive load is uniformly applied to the entire surface of the third plate material to crush the carbon black clumps immersed in methanol. Furthermore, the third plate material is lifted from the first suspension, and the first container is placed on the vibration table of a vibrator, and the vibrator is operated to repeatedly apply acceleration in three directions, forward / backward, left / right, and up / down, to the first container, thereby rearranging the crushed carbon black clumps in the methanol. That is, in the carbon black clusters, the size of the carbon black varies, and the size of the crushed carbon black also varies. For this reason, voids are formed in the crushed carbon black clusters. In order to fill these voids, the crushed carbon black clusters are rearranged and crushed again, so that the crushing of all the carbon black proceeds and the size of the crushed carbon black can be made closer to uniform. Furthermore, the third plate is covered again with the first suspension, and the compressive load is applied again uniformly to the entire surface of the third plate, to further crush the carbon black clusters immersed in methanol. Furthermore, the third plate is lifted again from the first suspension, and the acceleration in the three directions is applied again repeatedly to the first container. The pair of processes consisting of the process of applying the compressive load and the process of applying the acceleration are repeated, and when a repulsive force is generated in the third plate when the compressive load is applied to the third plate, it is determined that the crushing of the carbon black clusters immersed in methanol is completed, and the pair of processes is stopped. After this, the third plate is taken out of the first container.In other words, when the carbon black is crushed to a critical size, even if the crushed carbon black is compressed, no compressive stress is applied to the fine carbon black, so the fine carbon black is not crushed and a repulsive force is generated in the third plate. At this point, it is determined that the crushing of the carbon black cluster is complete. As a result, the carbon black is crushed to a size close to about 1 / 25 of its original size. The smallest unit of carbon black is an aggregate, which is a primary agglomeration of carbon particles. In carbon black, this aggregate is a collection of carbon particles in which carbon particles with a size of 10-100 nm are linked together in an irregular and complex shape (called a structure). The size of the aggregate is 100-500 nm, and the number of carbon particles is 100-1000. Therefore, the aggregate is extremely light and can be cut. This aggregate is easily entangled by the structure, forming an agglomerate, which is a secondary agglomeration of carbon particles and an agglomerate of aggregates. Therefore, by crushing carbon black, the agglomerates are also crushed, and the size of the agglomerates is crushed to a size close to 1 / 25 of the original size. Furthermore, the aggregate is also cut to a length shorter than 0.2 mm. In addition, by cutting the aggregates, after the methanol and alcohol are evaporated in the eighth step, the aggregates randomly overlap each other with a high degree of integration and precipitate in a sheet-like compact. Furthermore, the entire aggregate collection precipitated overlapping with each other is compressed, and all aggregates in the aggregate collection overlapping with a high degree of integration are frictionally welded together. Furthermore, the frictionally welded aggregate collection is frictionally welded to the sheet-like compact. Therefore, the adhesion force of the frictionally welded aggregate collection to the sheet-like compact is large. Furthermore, since the frictionally welded aggregate collection is thin at 3-6 μm and extremely lightweight, even if the frictionally welded aggregate collection is subjected to an impact force, the frictionally welded aggregate collection is not peeled off from the sheet-like compact. In the fifth step, a second suspension is prepared in which the entangled aggregates are dispersed in methanol. For this purpose, the entanglement of the aggregates in the crushed carbon black is separated. That is, all the aggregates are joined together by friction welding, and the aggregates joined by friction welding are friction-welded to a sheet-shaped compact, so that the entanglement of the aggregates in the crushed carbon black is once separated. Note that the entanglement of the aggregates is simply the contact of the aggregates with each other, and the bonding force between the entangled aggregates is extremely small. In other words, carbon black is mostly composed of agglomerates, which are aggregate aggregates, and the larger ones are powders that reach nearly 1 mm in size. For this reason, it is difficult to prepare a suspension in which the agglomerates are dispersed in methanol, and it is even more difficult to bond the agglomerates to each other by friction welding. For this reason, a homogenizer is operated in methanol, shock waves are continuously applied to the crushed agglomerates, and the parts where the aggregates are directly entangled are separated by the irradiation of shock waves, methanol is adsorbed to the separated parts, and the aggregates are entangled with each other through the methanol. Note that since the carbon black is crushed to the physically limiting size, the aggregates are cut to a length shorter than 0.2 mm. Therefore, by continuously applying shock waves, the entanglement between the aggregates can be easily released. As a result, the aggregates are entangled with each other through the methanol, and by further continuously applying shock waves, a second suspension is formed in which the entangled aggregates are dispersed in low-viscosity methanol. For this reason, a homogenizer is placed in the first container, the homogenizer is operated, and shock waves are repeatedly applied to the clusters of crushed carbon black through methanol. That is, when the homogenizer is operated in methanol, fine shock waves are continuously generated in the methanol, and the shock waves move through the methanol while exciting the molecules of methanol. On the other hand, since the molecular weight of methanol is small and the viscosity is low, the molecules of methanol are not easily excited by the shock waves, and the energy of the shock waves is not easily lost. For this reason, fine shock waves are efficiently and repeatedly irradiated through the methanol to the clusters of agglomerates immersed in the methanol. As a result, fine shock waves are repeatedly irradiated to the sites where the aggregates are directly entangled with each other, and since the aggregates are extremely light materials and the bonding strength between the entangled aggregates is weak, the directly entangled sites are once released, and methanol is adsorbed to the sites of the aggregates where the entanglement has been released. Furthermore, shock waves are repeatedly applied, and the clusters of aggregates entangled through the methanol are dispersed in the methanol. In addition, the aggregates have an irregular and complex structure in which carbon particles are strung together, and the size of each aggregate and the shape of the structure of each aggregate are different. Therefore, even if the shock waves generated by the homogenizer device are repeatedly irradiated to the agglomerates, all the parts where the aggregates are entangled in the aggregate collection are separated, and the aggregate collection is separated into individual aggregates, and the separated aggregates cannot be dispersed in methanol. In other words, the separation of the entanglement of the aggregates by the homogenizer device is a process of adsorbing methanol to the parts where the aggregates are entangled, and further dispersing the aggregate collection entangled through methanol in methanol. Therefore, in the aggregate collection in which the aggregates are entangled through methanol, the entangled aggregates are not joined to each other, and the aggregates entangled through methanol are dispersed in methanol. Therefore, in the sixth step, by mixing the second suspension with an alcohol that is soluble or miscible in methanol, the aggregates are entangled with each other via the dissolution or mixture in which the alcohol is dissolved in methanol, and a third suspension can be created in which a collection of the entangled aggregates is dispersed in the dissolution or mixture. In addition, when an ultrasonic homogenizer is used as the homogenizer, a huge number of bubbles smaller than the size of the cut aggregates are generated at the same time, and then the bubbles disappear almost at the same time. The generation and disappearance of the bubbles occurs repeatedly according to the generation cycle of the ultrasonic waves, and the generation and disappearance of the bubbles are repeated in low-viscosity methanol (this phenomenon is called cavitation). Shock waves generated when the bubbles burst are continuously generated in low-viscosity methanol, and the shock waves are hardly absorbed and are continuously irradiated to the fine parts of the agglomerates, so that the parts where the aggregates are directly entangled with each other are separated in a short time, and methanol is adsorbed to the separated parts. Therefore, the ultrasonic homogenizer repeats the generation and disappearance of bubbles according to the generation cycle of the ultrasonic waves, so that the parts where the aggregates are directly entangled with each other can be separated in a short time. In the sixth step, the aggregates are entangled with each other through a solution or mixture in which an alcohol having a viscosity of 3-6 mPa·sec at 20° C. is dissolved in methanol, and a collection of the entangled aggregates is dispersed in the solution or mixture to prepare a third suspension. For this purpose, an alcohol having three properties, namely, a first property of being soluble or miscible in methanol, a second property of having a viscosity 9-20 times that of methanol, and a third property of having a boiling point higher than that of methanol and lower than 200° C., is mixed into the second suspension in the first container in such a ratio that the viscosity of the second suspension in the first container increases by 5-10 times. As a result, the alcohol dissolves or becomes miscible with methanol, the viscosity of the solution or mixture of the alcohol dissolved in methanol increases to 3-6 mPa·sec at 20°C, the aggregates become entangled through the solution or mixture, and a third suspension is created in which a collection of entangled aggregates is dispersed in the solution or mixture. As a result, in the seventh step, when the sheet-like molded product created in the first step is immersed in the solution or mixture, the solution or mixture is adsorbed onto the surface of the sheet-like molded product to a thickness according to the viscosity of the solution or mixture. In the seventh step, the sheet-like molded product produced in the first step is immersed in the solution or mixture, so that the solution or mixture is adsorbed on the surface of the sheet-like molded product to a thickness according to the viscosity of the solution or mixture. In the eighth step, the entire sheet-like compact is covered with a collection of aggregates bonded by friction welding. For this purpose, a third container is prepared in which each plate constituting the four sides of a container having a rectangular bottom shape has a function of moving parallel to the inside of the container in a direction perpendicular to the sides. Next, the first plate material created in the second step is placed in the third container so that the multiple protrusions formed on the surface are on top. Furthermore, the sheet-like compact immersed in the third suspension in the seventh step is placed on the first plate material so that the multiple protrusions formed on the first plate material overlap the multiple grooves through which hydrogen gas passes formed in the sheet-like compact created in the first step. Furthermore, the second plate material is placed on the sheet-like compact immersed in the third suspension so that the multiple protrusions formed on the second plate material created in the third step overlap the multiple grooves through which oxygen gas or air passes formed in the sheet-like compact created in the first step. After that, a compressive load is evenly applied to the entire surface of the second plate material, and the temperature of the third container is raised to the boiling point of the alcohol. Furthermore, each plate material constituting the upper and lower side surfaces of the third container is moved in parallel to the inside of the third container at the same time, and the upper and lower side surfaces of the sheet-like molded body immersed in the third suspension are compressed with a compressive stress corresponding to the compressive load, and then each plate material constituting the upper and lower side surfaces is returned to its original position. Furthermore, each plate material constituting the left and right side surfaces of the third container is moved in parallel to the inside of the third container at the same time, and the left and right side surfaces of the sheet-like molded body immersed in the third suspension are compressed with a compressive stress corresponding to the compressive load, and then each plate material constituting the left and right side surfaces is returned to its original position. By these processes, first, methanol and alcohol are evaporated from the third suspension in order according to the boiling point, and the sheet-like compact immersed in the third suspension is covered with a collection of aggregates in which the aggregates are entangled with each other. Next, compressive stress is applied to the surface and side of the sheet-like compact in order, and the entire collection of entangled aggregates covering the sheet-like compact is compressed, and the collection of entangled aggregates overlaps with each other with a high degree of integration. Further compressive stress is applied, and the aggregates are elastically deformed so as to fill the small gaps in the collection of aggregates overlapping with each other with a high degree of integration, and the collection of aggregates overlaps with an even higher degree of integration. Further compressive stress is applied, and all the aggregates come into contact with each other, and the aggregates are joined by friction welding at the contact sites, and all the aggregates become a collection of aggregates joined to each other by friction welding. Furthermore, a compressive stress is applied to the friction-welded aggregate group, and the friction-welded aggregate group strongly contacts the surface and side of the sheet-like compact, the contact portion elastically deforms, and a part of this elastically deformed enters the unevenness of the surface and side of the sheet-like compact, and the friction-welded aggregate group is firmly bonded to the surface and side of the sheet-like compact. As a result, the entire sheet-like compact is covered with the aggregate group bonded by friction welding. Therefore, the bonding force between the aggregates in the aggregate group in which all the aggregates are bonded to each other by friction welding is large. In addition, the bonding force between the friction-welded aggregate group and the surface and side of the sheet-like compact is also large. Furthermore, since the aggregates joined by friction welding are thin and lightweight, and are firmly joined to the sheet-shaped compact over a certain area, even if an impact force is applied to the aggregates joined by friction welding, the aggregates joined by friction welding will not be peeled off from the sheet-shaped compact. In the ninth step, the same impact acceleration of 0.2-0.3 G is applied simultaneously to multiple locations on the back side of the bottom surface of the third container depending on the size of the container, and the sheet-like molded body sandwiched between the first plate and the second plate and covered with the aggregates bonded to the two plates is peeled off from the third container. In other words, since the bonding force between the bottom surface of the third container and the first plate is smaller than the bonding force between the first plate and the aggregates bonded by friction welding, the sheet-like molded body covered with the aggregates bonded to the two plates is peeled off from the bottom surface of the third container. Furthermore, the same impact acceleration of 0.2-0.3 G is applied simultaneously to multiple locations on the bottom surface of the first plate, and the sheet-like molded body covered with the aggregates is peeled off from the first plate. That is, the bonding force between the first plate and the aggregate group bonded by friction welding is smaller than the bonding force of the aggregate group bonded to the sheet-like molded body by friction welding, so the sheet-like molded body covered with the aggregate group is peeled off from the first plate. Finally, the same impact acceleration of 0.2-0.3 G is simultaneously applied to multiple points on the surface of the second plate, and the sheet-like molded body covered with the aggregate group is peeled off from the second plate. That is, the bonding force between the second plate and the aggregate group bonded by friction welding is smaller than the bonding force of the aggregate group bonded to the sheet-like molded body by friction welding, so the sheet-like molded body covered with the aggregate group is peeled off from the second plate. By carrying out all of these nine steps consecutively, a fuel cell separator plate is produced, which is made of a sheet-like compact covered with a collection of aggregates joined by friction welding. Next, the function and effect of the fuel cell separator plate made of the sheet-like molded article thus produced will be described. First, the fuel cell separator plate, which is made of a sheet-like compact covered with a collection of aggregates, has the electrical conductivity of carbon black. In other words, in the collection of aggregates in which all the aggregates are friction-welded, all the aggregates are connected to each other, so a path for electrons to move to the collection of aggregates is formed. This allows the fuel cell separator plate to have the electrical conductivity of carbon black. As a result, the electrical resistance of the separator plate required by the U.S. Department of Energy is 20 Ω cm or less, but due to the electrical resistance of carbon black, the electrical resistance of the fuel cell separator plate is two orders of magnitude lower than the electrical resistance of the separator plate required by the U.S. Department of Energy. Secondly, the synthetic resin sheet-shaped body is impermeable to hydrogen gas at atmospheric pressure, and therefore the fuel cell separator plate is impermeable to hydrogen gas at atmospheric pressure. Thirdly, a plurality of grooves through which hydrogen gas passes are formed on one surface of the sheet-like molded body, and a plurality of grooves through which oxygen gas or air passes are formed on the other surface of the sheet-like molded body, so that these grooves act as paths for supplying hydrogen gas and oxygen gas or air to the polymer membrane. Fourth, carbon black is not corroded by acids or alkalis and has better corrosion resistance than metals. In addition, the aggregates covering the sheet-shaped compact repel all liquids due to the surface tension of the liquid. As a result, no liquid can penetrate the sheet-shaped compact. Therefore, a fuel cell separator plate made of a sheet-shaped compact covered with aggregates has the corrosion resistance of carbon black and is resistant to protons (H + ) does not corrode or change over time even in highly oxidizing environments through which it passes. Fifth, because the sheet-shaped compact is as thin as 1.5-3 mm, it elastically deforms when subjected to an impact force, absorbing the impact force. In addition, the aggregates are as thin as 3-6 μm, extremely lightweight, and firmly bonded to the sheet-shaped compact, so they do not peel off from the sheet-shaped compact even when subjected to an impact force. Furthermore, if the sheet-shaped compact is formed from a synthetic resin with excellent impact resistance, the impact strength of the fuel cell separator plate can be further increased. Sixth, the thickness of the friction-welded aggregates is as thin as 3-6 μm, and the density of the carbon black is as low as 1.7-1.9 g / cm 3 Therefore, the friction-welded aggregate is extremely light. Therefore, the weight of a separator plate for a fuel cell is close to that of a sheet-shaped molded body. On the other hand, the density of synthetic resin is 0.9-1.6g / cm 3 The density of the fiber-reinforced resin is 1.5-1.7g / cm 3 The density of aluminum is 2.7g / cm 3 Furthermore, because the thickness of the sheet-like molded body is as thin as 1.5 to 3 mm, the weight of the fuel cell separator plate is significantly lighter than that of conventional fuel cell separator plates. Seventh, a sheet-like molded body made of a synthetic resin can be molded continuously and inexpensively into molded bodies of the same shape. Carbon black is also an inexpensive industrial material. Furthermore, methanol and alcohol are general-purpose organic solvents. All of the nine steps for producing a fuel cell separator plate made of a sheet-like molded body are extremely simple. For this reason, a fuel cell separator plate made of a sheet-like molded body covered with a collection of aggregates can be produced inexpensively. These seven effects solve all five of the problems described in paragraph 7.
[0010] The method of making a separator plate for a fuel cell according to paragraph 8, The method for producing a separator plate for a fuel cell comprises using acetylene black as the carbon black described in paragraph 8, continuously carrying out all of the nine steps described in paragraph 8, and forming a sheet-like molded body covered with a collection of aggregates of the acetylene black, the aggregates being joined by friction welding.
[0011] In other words, the characteristics of carbon black vary greatly depending on the manufacturing method, and carbon black is classified according to the name of the manufacturing method. The properties of carbon black vary depending on the manufacturing method. Furnace black is carbon black produced by incomplete combustion of oil or gas in high-temperature gas, and is subdivided into oil furnaces and gas furnaces depending on the raw material burned. Among furnace blacks, Ketjen black uses oil made of hydrocarbons as the raw material, and produces carbon black by incomplete combustion of the oil. Among carbon blacks, Ketjen black has the largest specific surface area and DPB (dibutyl phthalate) absorption, and its electrical conductivity is second only to acetylene black. In other words, Ketjen black has a hollow body formed by the structure of an arc, and the electrical conductivity of Ketjen black increases as electrons move through the arc-shaped structure. Other types of carbon black include channel black, which is made by burning natural gas and scraping off the deposits that form on channel steel; acetylene black, which is obtained by pyrolyzing acetylene gas; and thermal black, which is produced by repeatedly burning and decomposing gas in a heat-storing furnace. Acetylene black is produced using acetylene gas, which has the highest purity among the raw materials for carbon black, and therefore has the fewest impurities among carbon blacks, and also has the most developed structure and primary particles. For this reason, acetylene black has the highest electrical conductivity among carbon blacks. Therefore, a fuel cell separator plate having a configuration in which a sheet-shaped molded body is covered with a group of acetylene black aggregates bonded by friction welding has better electrical conductivity than a fuel cell separator plate using other carbon blacks. In addition, since the structure and primary particles are the most developed, acetylene black aggregates are easily entangled, and once entangled, the aggregates are difficult to separate. Therefore, the mechanical strength of the group of acetylene black aggregates bonded by friction welding is higher than that of the group of aggregates using other carbon blacks. For this reason, acetylene black is suitable as the carbon black constituting the fuel cell separator plate described in paragraph 8. Acetylene black, for example, has a bulk density of 0.04 g / cm 3 There is a powder product available with an electrical resistivity of 0.21 Ω·cm. In addition, in the aggregate collection where all the aggregates are friction-welded, all the aggregates are connected to each other, so a path for electrons to move to the aggregate collection is formed. This gives the fuel cell separator plate the electrical conductivity of acetylene black. As a result, the electrical resistance of the separator plate required by the U.S. Department of Energy is 20 Ωcm or less, but due to the electrical resistance of acetylene black, the electrical resistance of the fuel cell separator plate is two orders of magnitude lower than the electrical resistance of the separator plate required by the U.S. Department of Energy.
[0012] The method for producing a separator plate for a fuel cell according to paragraph 8 comprises: The method for producing a separator plate for a fuel cell includes molding a sheet-like molded body made of the synthetic resin described in the first step of paragraph 8 using one type of synthetic resin selected from the group consisting of polycarbonate resin, ultra-high molecular weight polyethylene resin, and fiber-reinforced resin, and then continuously carrying out all of the processes described in the second to ninth steps of paragraph 8 to produce a separator plate for a fuel cell having a configuration in which the sheet-like molded body made of one type of synthetic resin selected from the group consisting of polycarbonate resin, ultra-high molecular weight polyethylene resin, and fiber-reinforced resin is covered with a collection of aggregates joined by friction welding.
[0013] That is, among various synthetic resins, polycarbonate resin, ultra-high molecular weight polyethylene resin, and fiber reinforced resin have significantly higher impact strength than other synthetic resins. That is, the Izod impact strength is 93-98kJ / m for polycarbonate resin. 2 98kJ / m for ultra-high molecular weight polyethylene resin 2 100-160kJ / m for various fiber reinforced resins 2 It is. The Izod impact strength of the synthetic resins other than those mentioned above is, for example, 2.9-9.8 kJ / m for polyvinyl chloride resin. 2 2.9-7.8kJ / m for polypropylene resin 2 15-49kJ / m for ABS resin 2 and 1.4-2.2kJ / m for acrylic resin.2 , and polyethylene terephthalate resin is 1.4-3.8kJ / m 2 3.9-14kJ / m for nylon 66 resin 2 , and 6.9-12kJ / m for polyacetal resin. 2 , and 3.1-7.4kJ / m for polyphenylene sulfide resin. 2 and 14-16kJ / m for polytetrafluoroethylene resin. 2 Therefore, polycarbonate resin, ultra-high molecular weight polyethylene resin, and fiber reinforced resin have a much higher impact strength than other synthetic resins. Ultra-high molecular weight polyethylene resin is a polyethylene resin whose molecular weight, which is usually 20,000-300,000, has been increased to 1,000,000-7,000,000. Fiber-reinforced resin is a resin material in which glass fiber, carbon fiber, Zylon fiber, boron fiber, or aramid fiber is compounded with polyester resin, epoxy resin, vinyl ester resin, or phenol resin, and various strengths, heat resistance, and flame retardancy are significantly improved compared to the base synthetic resin. Various strengths, heat resistance, and flame retardancy are improved according to the volume ratio of the fiber. Glass fiber-reinforced plastic GFRP, which is a compound of unsaturated polyester resin and glass fiber, is the cheapest. For example, GFRP with 30% weight ratio of glass fiber with a glass length of 25 mm increases the impact strength of unsaturated polyester resin by more than 10 times. Therefore, a sheet-like molded body made of the synthetic resin described in the first step of paragraph 8 is molded using polycarbonate resin, ultra-high molecular weight polyethylene resin, or fiber-reinforced resin, and then all of the processes in the second to ninth steps of paragraph 8 are carried out continuously to produce a fuel cell separator plate in which the sheet-like molded body made of polycarbonate resin, ultra-high molecular weight polyethylene resin, or fiber-reinforced resin is covered with a collection of aggregates joined by friction welding.Although the sheet-like molded body is thin at 1.5-3 mm, the fuel cell separator plate has high impact strength.
[0014] The method of making a separator plate for a fuel cell according to paragraph 8, Alcohols that have the three properties described in paragraph 8 are 2-methyl-1-butanol, A method for producing a separator plate for a fuel cell, comprising using any one type of alcohol selected from the group consisting of 3-pentanol, 1-octanol, isooctanol, 2-ethyl-1-hexanol, 1-hexanol, 1-heptanol, and 2-ethyl-1-hexanol as an alcohol having the three properties described in paragraph 8, carrying out all of the nine treatments described in paragraph 8 consecutively, and producing a separator plate for a fuel cell having a configuration in which a collection of aggregates joined by friction welding covers a sheet-like molded body.
[0015] In other words, there are alcohols consisting of 2-methyl-1-butanol, 3-pentanol, 1-octanol, isooctanol, 2-ethyl-1-hexanol, 1-hexanol, 1-heptanol, and 2-ethyl-1-hexanol that have the three properties described in paragraph 8, namely, the first property of being soluble or miscible in methanol, the second property of having a viscosity 9 to 20 times that of methanol, and the third property of having a boiling point higher than that of methanol and lower than 200°C. 2-Methyl-1-butanol, CH3CH2CH(CH3)CH2OH, is miscible in methanol, has a viscosity of 5.1 mPa·s at 25°C, which is 9.4 times the viscosity of methanol at 25°C, and has a boiling point of 128°C. It is an alcohol that combines the three properties described in paragraph 8. 3-Pentanol, CH3CH2CHOHCH2CH3, is soluble in methanol, has a viscosity of 6.7 mPa·s at 20°C, which is 11.4 times the viscosity of methanol at 20°C, and has a boiling point of 116°C, making it an alcohol that combines the three properties described in paragraph 8. 1-Octanol, CH3(CH2)6CH2OH, is miscible in methanol, has a viscosity of 7.3 mPa·s at 25°C, which is 13.5 times the viscosity of methanol at 25°C, and has a boiling point of 195°C. It is an alcohol that combines the three properties described in paragraph 8. Isooctanol, CH3(CH2)3CH2CH2CH3CH2OH, is soluble in methanol, has a viscosity of 12.0 mPa·s at 20°C, which is 20.3 times the viscosity of methanol at 20°C, and has a boiling point of 188°C. It is an alcohol that combines the three properties described in paragraph 8. 2-Ethyl-1-hexanol, CH3(CH2)3CH(CH2CH3)CH2OH, is soluble in methanol, has a viscosity of 10.0 mPa·s at 20°C, which is 16.9 times the viscosity of methanol at 20°C, and has a boiling point of 182°C. It is an alcohol that combines the three properties described in paragraph 8. 1-Hexanol, CH3(CH2)3OH, is soluble in methanol, has a viscosity of 5.2 mPa·s at 20°C, which is 8.8 times the viscosity of methanol at 20°C, and has a boiling point of 157°C. It is an alcohol that combines the three properties described in paragraph 8. 1-Heptanol, CH3(CH2)5CH2OH, is soluble in methanol, has a viscosity of 5.8 mPa·s at 25°C, which is 10.7 times the viscosity of methanol at 25°C, and has a boiling point of 176°C. It is an alcohol that combines the three properties described in paragraph 8. 2-Ethyl-1-hexanol, CH3(CH2)3CH(C2H5)CH2OH, is soluble in methanol, has a viscosity of 9.8 mPa·s at 20°C, which is 16.6 times the viscosity of methanol at 20°C, and has a boiling point of 185°C. It is an alcohol that combines the three properties described in paragraph 8. Therefore, by using any one of these alcohols as an alcohol having the three properties described in paragraph 8 and performing all of the nine steps described in paragraph 8 consecutively, a fuel cell separator plate is produced that is configured such that a collection of aggregates joined by friction welding are covered with a sheet-shaped compact. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is an explanatory diagram illustrating a cross section of a sheet-like molded product covered with a collection of acetylene black aggregates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Example 1 In this example, polycarbonate resin pellets (Panlite from Teijin Limited) were used to extrude a sheet-like molded body measuring 30 cm x 30 cm x 2 mm (thickness). On one surface of the molded body, multiple grooves measuring 30 cm (length) x 5 mm (width) x 1 mm (depth) were formed at regular intervals as grooves through which hydrogen gas can pass, and on the other surface of the molded body, multiple grooves measuring 30 cm (length) x 5 mm (width) x 1 mm (depth) were formed at the same intervals as above in areas where the grooves were not formed as grooves through which oxygen gas or air can pass. The Charpy impact strength of Panlite with a notch is 76 kJ / m 2 and big. On the other hand, the material of the synthetic resin constituting the sheet-shaped molded body is not limited to polycarbonate resin. As described in paragraph 13, polycarbonate resin is a type of synthetic resin with excellent impact resistance. Therefore, polycarbonate resin is effective in producing a separator plate for a fuel cell with excellent impact resistance. To further increase the impact resistance, a resin containing glass fiber may be used. On the other hand, if impact resistance is not required for the separator plate for a fuel cell, a sheet-shaped molded body is formed from synthetic resins made of various materials. In addition, the shape of the grooves formed on the surface of the sheet-like molded body is not limited to the elongated rectangle described above. Since the grooves are formed by molding synthetic resin, the shape of the grooves is not restricted. Furthermore, when the grooves are formed by machining, the cost of forming the grooves varies greatly depending on the shape and number of the grooves, whereas when the grooves are formed by molding synthetic resin, the cost of the mold varies depending on the shape and number of the grooves, but the cost of molding the grooves does not change.
[0018] Example 2 In this example, a sheet-like molded body having a size of 30 cm x 30 cm x 4 mm (thickness) was molded by extrusion molding using the polycarbonate resin pellets of Example 1. Note that a plurality of protrusions having a shape overlapping the plurality of grooves were formed at positions corresponding to the plurality of grooves through which hydrogen gas passes formed in the sheet-like molded body of Example 1. Note that the material of the sheet-like molded body is not limited to polycarbonate resin.
[0019] Example 3 In this example, a sheet-like molded body having a size of 30 cm x 30 cm x 4 mm (thickness) was molded by extrusion molding using the polycarbonate resin pellets of Example 1. Note that a plurality of protrusions having a shape overlapping the plurality of grooves were formed at positions corresponding to the plurality of grooves through which oxygen gas or air passes formed in the sheet-like molded body of Example 1. Note that the material of the sheet-like molded body is not limited to polycarbonate resin.
[0020] Example 4 In this example, acetylene black is used as the carbon black, and the acetylene black is crushed to a maximum size in methanol, and the crushed acetylene black is dispersed in methanol to prepare a suspension. First, 40 g of acetylene black (Li-100, a product of Denka Co., Ltd.) and 80 g of industrial grade 1 methanol were filled into a container, and the methanol was stirred to immerse the acetylene black in the methanol. The acetylene black used had an average particle size of 35 nm and a specific surface area of 68 m 2 / g and is composed of primary particles with an iodine adsorption capacity of 92mg / g. Acetylene black also has a bulk density of 0.04g / ml and an electrical resistivity of 0.21Ω·cm, making it the most conductive of all carbon blacks. After this, a flat plate was placed on top of the container, and nine 2 kg weights were placed on the plate at equal intervals. The weights and the plate were then removed, and the container was fixed on a vibration table, and a vibration acceleration of 2 G was repeatedly applied to the container in three directions: front-back, left-right, and up-down. After repeating this pair of processes of applying a compressive load and applying a vibration acceleration five times, the weight was placed on the flat plate, but since there was no movement of the flat plate at all, it was determined that the acetylene black had been crushed to the limit size in methanol, and the pair of processes was stopped. In addition, an ultrasonic homogenizer (LUH150, product of Yamato Scientific Co., Ltd.) was operated in the methanol in the container, and a 20 kHz ultrasonic signal was applied for 15 minutes to create a suspension in which aggregates in which the aggregates were entangled with each other were dispersed in methanol.
[0021] Example 5 In this example, the suspension prepared in Example 4 is mixed with 3-pentanol described in paragraph 15 to increase the viscosity of the suspension to 6.8 times the viscosity of methanol, and a new suspension is prepared in which entangled aggregates are dispersed in a solution of 3-pentanol dissolved in methanol. Furthermore, the sheet-like molded body prepared in Example 1 is immersed in the new suspension, and the solution of 3-pentanol dissolved in methanol is attached to the sheet-like molded body. For this reason, 101 g of 3-pentanol was mixed with the suspension prepared in Example 4 to prepare a new suspension in which the entangled aggregates were dispersed in a solution in which 3-pentanol was dissolved in methanol. After this, the sheet-like molded product prepared in Example 1 was immersed in the new suspension, and the sheet-like molded product with the solution in which 3-pentanol was dissolved in methanol attached was taken out. The alcohol that increases the viscosity of the suspension to 5-10 times that of methanol is not limited to 3-pentanol. By using various types of alcohols described in paragraph 15 and changing the mixing ratio of the alcohol to the suspension depending on the viscosity of the alcohol, a solution or mixture in which an alcohol with a viscosity of 3-6 mPa·sec at 20°C described in paragraph 8 is dissolved or mixed in methanol can be obtained.
[0022] Example 6 In this embodiment, a collection of aggregates adsorbed to the sheet-like compact prepared in Example 1 is friction-welded, and the friction-welded collection of aggregates is then friction-welded to the front and side surfaces of the sheet-like compact, covering the entire sheet-like compact with the collection of aggregates joined by friction welding. First, a container was prepared that had an outer shape of 35 cm x 35 cm, a depth of 2 cm, and a width of 2 cm, and had four plates that could move in parallel in a direction perpendicular to the sides to the inside of the container. Next, the sheet-like molded product prepared in Example 2 was placed 1 cm away from the four sides of the container, with multiple protrusions facing upward. Next, the sheet-like molded product prepared in Example 5 and immersed in the new suspension was placed over the protrusions of the sheet-like molded product prepared in Example 2 so that the grooves through which hydrogen gas passes of the sheet-like molded product prepared in Example 5 and immersed in the new suspension were overlapped. Furthermore, the sheet-like molded body prepared in Example 3 was placed over the sheet-like molded body immersed in the new suspension so that the multiple protrusions of the sheet-like molded body prepared in Example 3 overlapped with the multiple grooves of the sheet-like molded body immersed in the new suspension through which oxygen gas or air passes. Thereafter, nine weights weighing 2 kg were placed at equal intervals on the surface of the sheet-like molded product prepared in Example 3. Furthermore, the container was heated to 116° C., which is the boiling point of 3-pentanol. Furthermore, each plate material constituting the upper and lower side surfaces of the container was moved in parallel to the inside of the container at the same time, and the upper and lower side surfaces of the sheet-like molded body immersed in the new suspension were compressed with a compressive stress equivalent to the compressive load applied to the sheet-like molded body prepared in Example 3, and then each plate material constituting the upper and lower side surfaces was returned to its original position. Furthermore, each plate material constituting the left and right side surfaces of the container was moved in parallel to the inside of the container at the same time, and the left and right side surfaces of the sheet-like molded body immersed in the new suspension were compressed with a compressive stress equivalent to the compressive load applied to the sheet-like molded body prepared in Example 3, and then each plate material constituting the left and right side surfaces was returned to its original position. After that, an impact acceleration of 0.3 G was simultaneously applied to nine equally spaced points on the bottom surface of the container, and the sheet-like molded body sandwiched between the two sheet-like molded bodies and immersed in the new suspension bonded to the two molded bodies was peeled off from the container. Furthermore, an impact acceleration of 0.3 G was simultaneously applied to nine points on the bottom surface of the sheet-like molded body prepared in Example 2, and the sheet-like molded body immersed in the new suspension bonded to the two molded bodies was peeled off from the sheet-like molded body prepared in Example 2. Finally, an impact acceleration of 0.3 G was simultaneously applied to nine points on the surface of the sheet-like molded body prepared in Example 3, and the sheet-like molded body immersed in the new suspension was peeled off from the sheet-like molded body prepared in Example 3 to obtain a sheet-like molded body covered with a collection of aggregates. The surface of the sheet-like molded body covered with a collection of aggregates was observed using an electron microscope. An extremely low accelerating voltage SEM owned by JFE Techno-Research Corporation was used as the electron microscope. This device allows surface observation at extremely low accelerating voltages starting from 100V, and allows the surface of the sample to be observed directly without forming a conductive coating. First, secondary electron beams between 900-1000 volts were extracted from the electron beam reflected from the surface and image processing was performed. Fine black material was layered with a high degree of integration, overlapping with no gaps. Next, energies between 900-1000 volts were extracted from the electron beam reflected from the surface and image processing was performed, and the material of the black material was analyzed based on the shade of the image. As no shade was observed, it was found to be composed of a single atom. Furthermore, the energy and intensity of characteristic X-rays from the surface were image processed and the type of elements that make up the black material were analyzed. The black material was composed only of carbon atoms. From the above observation results, it was found that aggregates of acetylene black were stacked at a high density over the entire surface of the sheet-like molded body. Next, the surface resistance of the sheet-like molded body covered with the aggregates was measured at multiple points using a surface resistance meter (e.g., a surface resistance meter ST-4 from SIMCO Japan Co., Ltd.) The surface resistivity was 1.0 Ω, which means that the molded body had a resistance close to the resistivity of acetylene black, 0.21 Ω cm. Furthermore, the hydrogen gas permeability of the sheet-like molded body covered with a collection of aggregates was measured using a gas permeability measuring device using differential pressure gas chromatography, and it was found that hydrogen gas did not permeate at atmospheric pressure. In addition, a sheet-like molded body covered with aggregates was allowed to drop from a height of 2 m without being damaged, demonstrating that the molded body has a certain level of mechanical strength even with a plate thickness of 2 mm. Note that, to further increase the mechanical strength of the sheet-like molded body, it may be molded from a fiber-reinforced resin having further impact resistance as described in paragraph 13. Finally, a part of the sheet-like molded product covered with the aggregates of acetylene black was cut, and the cut surface was observed with the electron microscope described above. It was found that the aggregates of acetylene black covered the surface of the sheet-like molded product to a thickness of 4 μm. Figure 1 shows an enlarged schematic of the cut surface. 1 is the aggregates of laminated acetylene black, and 2 is the molded product made of polycarbonate resin. [Explanation of symbols]
[0023] 1. Acetylene black aggregates 2. Molded body made of polycarbonate resin
Claims
1. A method for producing a separator plate for a fuel cell, which has a structure in which a sheet-like molded body made of a synthetic resin is entirely covered with a collection of carbon black aggregates bonded by friction welding, comprises the steps of: A first step of forming a sheet-like molded body made of a synthetic resin having a plurality of grooves formed on one surface through which hydrogen gas passes and a plurality of grooves formed on the other surface through which oxygen gas or air passes; a second step of molding a first plate material made of synthetic resin, the first plate material having the same shape as the sheet-like molded body, a thickness greater than that of the sheet-like molded body, and having a plurality of protrusions formed at positions corresponding to the plurality of grooves through which hydrogen gas passes, the plurality of protrusions being shaped to overlap the plurality of grooves formed in the sheet-like molded body; a third step of molding a second plate material made of synthetic resin, the second plate material having the same shape as the sheet-like molded body, a thickness greater than that of the sheet-like molded body, and having a plurality of protrusions formed at positions corresponding to the plurality of grooves through which oxygen gas or air passes, the plurality of protrusions being shaped to overlap the plurality of grooves formed in the sheet-like molded body; A first suspension is prepared by placing carbon black clumps and methanol in a quantity greater than the weight of the carbon black clumps in a first container, stirring the methanol, and immersing the carbon black clumps in the methanol. Thereafter, a third plate material that covers the entire surface of the first suspension is placed on the first suspension, and a compressive load is evenly applied to the entire surface of the third plate material to crush the carbon black clumps immersed in the methanol. The first container is placed on a vibration table of a vibrator, and the vibrator is operated to repeatedly apply vibration acceleration in three directions, i.e., forward / backward, left / right, and up / down, to the first container, and the crushed carbon black clumps are crushed. a fourth step of applying the compressive load evenly to the entire surface of the third plate material again to further crush the crushed carbon black clumps in the methanol; and applying the vibration acceleration in the three directions to the first container again repeatedly. The pair of steps consisting of the step of applying the compressive load and the step of applying the vibration acceleration are repeated, and when a repulsive force is generated in the third plate material when the compressive load is applied to the third plate material, it is determined that the crushing of the carbon black clumps in the methanol is completed, and the pair of steps are stopped. Then, the third plate material is removed from the first container. a fifth step of disposing a homogenizer device in the first container, operating the homogenizer device in the first suspension, and repeatedly applying shock waves to the clusters of carbon black after the crushing process via the methanol to entangle aggregates in the carbon black after the crushing process via the methanol, thereby preparing a second suspension in which the clusters of entangled aggregates are dispersed in the methanol; a sixth step of mixing an alcohol having three properties, namely, a first property of being soluble or miscible in methanol, a second property of having a viscosity 9-20 times that of methanol, and a third property of having a boiling point higher than that of methanol and lower than 200°C, with the second suspension, increasing the viscosity of a solution in which the alcohol is dissolved in the methanol or a mixture in which the alcohol is mixed to 3-6 mPa·sec at 20°C, and entangling the entangled aggregate groups via the solution or mixture, thereby preparing a third suspension in which the entangled aggregate groups are dispersed in the solution or mixture; a seventh step of pouring the third suspension into a second container having a bottom surface slightly larger than the sheet-like molded body produced in the first step, and further immersing the sheet-like molded body in the third suspension; The first plate material prepared in the second step is placed in a third container in which each plate material constituting the four side surfaces of the container has a function of moving parallel to the inside of the container in a direction perpendicular to the side surface, with the multiple protrusions formed on the first plate material facing up. Further, the sheet-like molded body immersed in the third suspension is placed on top of the first plate material so that the multiple protrusions formed on the first plate material overlap with the multiple grooves formed in the sheet-like molded body through which hydrogen gas passes. Further, the second plate material prepared in the third step is formed The second plate is placed on the sheet-like molded body immersed in the third suspension so that the multiple protrusions overlap the multiple grooves formed in the sheet-like molded body through which oxygen gas or air passes. Thereafter, a compressive load is evenly applied to the entire surface of the second plate, and the temperature of the third container is raised to the boiling point of the alcohol. Furthermore, each plate constituting the upper and lower side surfaces of the third container is simultaneously moved in parallel to the inside of the third container, and the upper and lower side surfaces of the sheet-like molded body immersed in the third suspension are heated to the boiling point of the alcohol. The left and right side surfaces of the sheet-like molded body immersed in the third suspension are compressed with a compressive stress corresponding to the compressive load, and then the plate materials constituting the upper and lower side surfaces are returned to their original positions. Furthermore, the plate materials constituting the left and right side surfaces of the third container are simultaneously translated toward the inside of the third container, and the left and right side surfaces of the sheet-like molded body immersed in the third suspension are compressed with a compressive stress corresponding to the compressive load, and then the plate materials constituting the left and right side surfaces are returned to their original positions. As a result, the methanol and the alcohol are vaporized from the third suspension and are mixed into the third suspension. an eighth step in which the immersed sheet-like compact is entirely covered with a collection of entangled aggregates, a compressive stress is applied to the front and side surfaces of the sheet-like compact, the entangled aggregates covering the sheet-like compact are friction-welded to each other, the compressive stress is applied to the friction-welded collection of aggregates, the friction-welded collection of aggregates is friction-welded to the front and side surfaces of the sheet-like compact, and the sheet-like compact is entirely covered with the collection of aggregates joined by friction welding; a ninth step of simultaneously applying the same impact acceleration to a plurality of positions on the bottom surface of the third container, and peeling off from the third container a sheet-like molded body covered with the aggregate collection sandwiched between the first plate and the second plate and joined to the two plates; simultaneously applying the same impact acceleration of the same magnitude to a plurality of positions on the bottom surface of the first plate, and peeling off from the first plate; and finally, simultaneously applying the same impact acceleration of the same magnitude to a plurality of positions on the surface of the second plate, and peeling off from the second plate; By carrying out all of these nine steps consecutively, a method for producing a fuel cell separator plate is achieved in which a fuel cell separator plate is produced, which consists of a sheet-like compact covered with a collection of aggregates joined by friction welding.
2. The method for producing a separator plate for a fuel cell according to claim 1 comprises the steps of: This method for producing a separator plate for a fuel cell comprises using acetylene black as the carbon black described in claim 1, continuously carrying out all of the nine steps described in claim 1, and forming a sheet-like molded body covered with a collection of aggregates of the acetylene black, the aggregates being joined by friction welding.
3. The method for producing a separator plate for a fuel cell according to claim 1 includes the steps of: This is a method for producing a separator plate for a fuel cell, comprising the steps of: forming a sheet-like molded body made of the synthetic resin described in the first step of claim 1 using one type of synthetic resin selected from the group consisting of polycarbonate resin, ultra-high molecular weight polyethylene resin, and fiber-reinforced resin; and continuously carrying out all of the treatments described in the second to ninth steps of claim 1 to produce a separator plate for a fuel cell, the sheet-like molded body made of one type of synthetic resin selected from the group consisting of polycarbonate resin, ultra-high molecular weight polyethylene resin, and fiber-reinforced resin, covered with a collection of aggregates joined by friction welding.
4. The method for producing a separator plate for a fuel cell according to claim 1 comprises the steps of: The alcohol having the three properties described in claim 1 is 2-methyl-1-butanol, The method for producing a separator plate for a fuel cell includes using any one type of alcohol selected from the group consisting of 3-pentanol, 1-octanol, isooctanol, 2-ethyl-1-hexanol, 1-hexanol, 1-heptanol, and 2-ethyl-1-hexanol as an alcohol having the three properties described in claim 1, continuously carrying out all of the treatments in the nine steps described in claim 1, and producing a separator plate for a fuel cell having a configuration in which a collection of aggregates joined by friction welding covers a sheet-like molded body.
Citation Information
Patent Citations
Separator for fuel cell having solid polymer electrolyte membrane
JP2004079536A
Separator for fuel cell and method for producing the same
WO1999049530A1